HUBUNGAN KECERDASAN EMOSIONAL DENGAN NILAI PRESTASI BELAJAR PAI DI SDN 04 CILILIN - Fitriati, Ajeng Seni (INTIHA: Islamic Education Journal, 2023)
Many people have held the opinion that having a high Intelligence quotient is necessary for achieving great academic success. But a wealth of research has conclusively shown that Intelligence quotient is not the only factor in academic achievement. Emotional intelligence is a significant additional element at work, include range of capabilities, including self-awareness, emotional control, self-motivation, empathy, and interpersonal connection abilities are almost all part of Islamic Education. The more emotionally intelligent a person is, the more profoundly it affects their academic success. In this study, students at SDN 04 Cililin in the Bandung Barat Regency will have their academic performance and emotional intelligence levels evaluated. Using a quantitative research methodology, data were collected using a random sampling technique employing questionnaires, using Excel and SPSS. Data analysis was done using the Pearson product-moment correlation method. With scores 40%, the analysis's findings showed that students' emotional intelligence levels were in the middle range. The study of the grades for Islamic Religious Education also showed that they were in the middle range. The percentage table, which shows that 82 of the sampled students is 22% fell into the minimum category, supports this observation. At a 5% level of significance, the correlation calculation produced a score of 0.761, indicating a significant strong between emotional intelligence levels and academic achievement. With a considerable contribution rate of 58,1%, this link had a major impact on academic success.